2020
DOI: 10.1159/000510908
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oral Myofunctional Therapy on Orofacial Myofunctional Status and Tongue Strength in Patients with Tongue Thrust

Abstract: <b><i>Introduction:</i></b> Tongue thrust is a frequent clinical condition characterized by abnormal patterns of movements and altered tongue posture on the mouth floor. It might contribute to determining alterations in the maxillofacial morphology and in the development of malocclusion. Several therapeutic options are available for treatment. In particular, the orofacial myofunctional therapy (OMT) is frequently adopted even if only few studies have analyzed its efficacy using validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…An initial screening of the titles and abstracts identified 47 studies. After reading the full texts, 33 studies [ 44 , 45 , 46 , 47 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ] were included, thus eliminating 14 studies [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 78 ] that did not meet the inclusion/exclusion criteria. The summary of the search strategy is depicted in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An initial screening of the titles and abstracts identified 47 studies. After reading the full texts, 33 studies [ 44 , 45 , 46 , 47 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ] were included, thus eliminating 14 studies [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 78 ] that did not meet the inclusion/exclusion criteria. The summary of the search strategy is depicted in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 14 intervention studies [ 44 , 45 , 46 , 47 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ], participants included dysphagic post-stroke subjects in 3 studies (21.4%) [ 45 , 46 , 60 ], older adults in 4 studies (28.6%) [ 47 , 61 , 62 , 63 ], and subjects with sleep breathing disorders in 4 studies (28.6%) [ 64 , 65 , 66 , 67 ]. Subjects with tongue thrust [ 68 ], as well as patients with Parkinson’s disease [ 69 ], were included in only 1 study (7.1%). Moreover, the sample in 1 out of 14 intervention studies (7.1%) was totally composed of HC without any reported pathologies [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kojima et al [21] suggested that orthognathic surgery can improve the malocclusion and skeletal jaw relationship and tongue-palate position during post-operative articulation. Considering tongue thrust, Mozzanica et al [22] also stated that patients with tongue thrust perform forward movements and interpose the tongue between their teeth while speaking and swallowing with consecutive pressure against the lingual surfaces of the anterior teeth and altered tongue position in the oral cavity. As in the present study, incorrect swallowing is related to the bone morphology named as the high palate; it may be possible that abnormal tongue activity is associated with some reduced contraction of the lower jaw elevator and by this, somewhat compensation mechanism activates the perioral muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with malocclusion seek treatment to improve aesthetics, psychosocial relationships, and quality of life (QOL) [1]. However, orthodontic treatment could also improve oral functions [2] and oral health [3]. Demand for orthodontic treatment and treatment outcome satisfaction is not necessarily in correlation with the objective malocclusion records and the clinician's opinion [4].…”
Section: Introductionmentioning
confidence: 99%